El rol del arbitraje de inversión en la implementación de las políticas de cambio climático - Gómez-Moreno, Juan Pablo (2022)
Nowadays, there is no doubt that one of the main issues of the global agenda is climate change. Conscious of such a reality, several actors of the society have been more closely involved in the debate on the protection of the environment and the reduction of those activities that contribute to diminishing it. Investment arbitration is a field that, even though it has not appeared active and directly in these discussions, keeps a close relationship with these issues and might play a fundamental role in the effectiveness of the implementation of climate change policies.Against this backdrop, this article focuses on studying the relationship between investment arbitration and climate change, explaining their points of contact and differences, to propose some thoughts on specific ways in which investor-State arbitration might contribute to the agenda on climate change.